Field evaluation of Standard Diagnostics' Bioline HIV/Syphilis Duo test among female sex workers in Johannesburg, South Africa. (6th May 2016) - Black, Vivian; Williams, Brian G; Maseko, Venessa; Radebe, Frans; Rees, Helen V; Lewis, David A
Abstract : Background: Point-of-care tests provide immediate results with the opportunity for same-day interventions with improved public health outcomes. A dual HIV/syphilis test enables early treatment of both diseases. Methods: We conducted a field evaluation of the Standard Diagnostics' SD Bioline HIV/Syphilis Duo test (SD Bioline) among female sex workers. SD Bioline was conducted on finger-prick blood according to manufacturer's instructions and compared with (i) Genscreen HIV1/2 (third generation) and Vironostika Ag/Ab (fourth generation) assays for HIV, and (ii) Treponema pallidum particle agglutination (TPPA) and rapid plasma reagin (RPR) assays for syphilis. A negative TPPA test was considered negative, a TPPA-confirmed RPR titre ≤1:4 as past infection and a TPPA-confirmed RPR titre ≥1:8 as active syphilis. Sensitivity, specificity, positive and negative predictive values were calculated. Results: Of 263 women recruited, 14 (5.3%) declined an HIV test. Among the remaining 249 women, 187 (75.1%) were HIV positive, 51 (20.5%) had syphilis antibodies with seven (2.8%) active infections. For HIV, the sensitivity and specificity were 98.9% (95% CI 95.8% to 99.8%) and 100% (95% CI 92.7% to 100%). For syphilis, the sensitivity and specificity were 66.7% (95% CI 52.0% to 78.9%) and 98.0% (95% CI 94.5% to 99.3%). Sera with high TPPA titres were more likely to test positive. Conclusions: In field conditions, while the SD Bioline test has high sensitivity and specificity for HIV and high specificity for syphilis, the test has lower sensitivity for syphilis than reported from laboratory evaluations. As the dual test detects only two thirds of syphilis cases, it should only be used in areas with weak screening programmes.